MRI Correlation of Radial Head Fractures and Forearm Injuries. (March 2017) - Awan, Hisham; Goitz, Robert
Background: Radial head fractures can be associated with soft tissue injuries of the forearm and wrist. The Essex-Lopresti injury can lead to significant morbidity, especially if the diagnosis is not made acutely. Better identification of such injuries is needed to allow optimal surgical treatment and prevent long-term sequelae. We used magnetic resonance imaging (MRI) to correlate the degree of soft tissue injuries with radial head fractures.Methods: Sixteen pairs of forearms with an associated radial head fracture in 15 patients prospectively underwent an MRI within 2 weeks of their injury. MRI findings were correlated with fracture type, associated soft tissue injury, and presence of symptomatic wrist pain.Results: According to the modified Mason classification, there were 8 type I, 5 type II, and 3 type III radial head fractures. Wrist pain was reported in 8 of 16 extremities, and 2 had associated wrist pathology, including an acute scaphoid fracture in 1 patient and a preexisting stage II scapholunate advanced collapse (SLAC) wrist in another patient. The MRI findings included an elbow effusion in all 16 patients, edema in the proximal third of the radius in 15 extremities, which extended to the middle third in 3 extremities, edema of the interosseous membrane (IOM) in 5 extremities, and edema of the soft tissues including the supinator and/or pronator quadratus in 13 extremities.Conclusions: Eighty percent of patients with edema of the IOM had associated wrist pain. Soft tissue injuries of the forearm did not correlate with the severity of the radial head fracture.